2006
DOI: 10.1002/cbm.618
|View full text |Cite
|
Sign up to set email alerts
|

Differences in personality and risk characteristics in sex, violent and general offenders

Abstract: The results from this study support the use of self-report inventories in assessing differences between offender groups. Such information may assist clinicians in prioritizing management and intervention strategies for those offenders, and in turn lower the risk of further offending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 25 publications
3
34
0
2
Order By: Relevance
“…In particular, the significant priming effect of violent picture was found in both participants with HA and MA, but not in LA. This result was in line with previous researches, which showed that the moderately aggressive and highly aggressive boys differed from the nonaggressive boys on attributional biases, and that severely aggressive displayed more social-cognitive dysfunctions than moderately and lowly aggressive boys (Bushman, 1995;Anderson, 1997;Lochman & Dodge, 1994;Widom, 1989;Virkkunen, Kallio, & Rawlings, 1994;Anderson, Anderson, Dill, & Deuser, 1998;Craig, Browne, Beech, & Stringer, 2006). Moreover, the result was in agreement with prior researches, and were also correspondent with the expected hypotheses, which assumed that individuals with HA had higher aggression than others (Bushman, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…In particular, the significant priming effect of violent picture was found in both participants with HA and MA, but not in LA. This result was in line with previous researches, which showed that the moderately aggressive and highly aggressive boys differed from the nonaggressive boys on attributional biases, and that severely aggressive displayed more social-cognitive dysfunctions than moderately and lowly aggressive boys (Bushman, 1995;Anderson, 1997;Lochman & Dodge, 1994;Widom, 1989;Virkkunen, Kallio, & Rawlings, 1994;Anderson, Anderson, Dill, & Deuser, 1998;Craig, Browne, Beech, & Stringer, 2006). Moreover, the result was in agreement with prior researches, and were also correspondent with the expected hypotheses, which assumed that individuals with HA had higher aggression than others (Bushman, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…Two major factors on which delinquents may be differentiated are the type and the severity of the offence they are charged with. In previous research, violent offenders had significantly more chaotic lifestyles and displayed greater psychopathology than sex or general offenders (Craig, Browne, Beech, & Springer, 2006). It seems likely that that a person who has committed a violent crime like aggravated battery or manslaughter could be dissimilar from persons charged with property offences or offences against morality in terms of personality dimensions such as neuroticism, lack of remorse, or impulsivity.…”
Section: Introductionmentioning
confidence: 90%
“…É consenso que os portadores de pedofilia podem manter seus desejos em segredo durante toda a vida sem nunca compartilhá-los ou torná-los atos reais; podem casar-se com mulheres que já tenham filhos ou atuar em profissões que os mantenham com fácil acesso a crianças, mas raramente causam algum mal [20][21][22] . Por outro lado, os molestadores de crianças, em sua maioria, apresentam motivações variadas para os seus crimes, que raramente têm origem em transtornos formais da preferência sexual 18,19,[23][24][25][26][27] . Acredita-se que a passagem da fantasia para a ação no caso dos pedófilos ocorre com maior frequência quando o indivíduo é exposto a estresse intenso, situações nas quais haja grande pressão psíquica, como discussão conjugal importante, demissão, aposentadoria compulsória etc.…”
Section: Caracterização Da Pedofilia: Abusadores Versus Molestadoresunclassified
“…Os abusadores caracterizam-se principalmente por atitudes mais sutis e discretas no abuso sexual, geralmente se utilizando de carícias, visto que em muitas situações a vítima não se vê violentada. Já os molestadores são mais invasivos, menos discretos e geralmente consumam o ato sexual contra a criança [20][21][22][23]25 . Há, ainda, autores que classificam os pedófilos baseados na preferência de gênero -homossexual, heterossexual ou bissexual -, enquanto outros preferem diferenciá-los por faixa etária -adolescentes, de meiaidade ou idosos 27 .…”
Section: Caracterização Da Pedofilia: Abusadores Versus Molestadoresunclassified